(untitled) (Colombia Medica, 1981)
The frequency of wounds on the fingertips and the functional loss they may represent create the necessity for a correct evaluation and treatment by the primary care physician. In their management, the following criteria must be emphasized: Keep the length of the finger, the skin sensitivity, and good functional-cosmetic appearance. The primary care steps are briefly explained. The different, easy, and complex therapeutic views in the management of wounds, as well as the techniques of coverage and the treatment of nail bed lessons, are also included.